IMPRISONMENT FOR IUU FISHING IN INDONESIAâ€™S EXCLUSIVE ECONOMIC ZONE: WHY IT SHOULD NOT BE IMPOSED - Alfons Zakaria (Arena Hukum, 2012)
Article 73(3) of LOSC emphasizes that â€œCoastal State penalties for violations of fisheries laws and regulations in the exclusive economic zone may not include imprisonment, in the absence of agreements to the contrary by the States concerned, or any other form of corporal punishment.â€ Article 93 ofthe Indonesian Fisheries Act Nomor 31 2004 as revised by the Act Nomor 45 2009, however, imposes imprisonment for IUU fishing committed in the Indonesian EEZ. It can be seen that there is a clear contradiction in provisions between Article 93 of the Act Nomor 31 2004 and Article 73(3) of the LOSC. On the other side, Indonesia is a state party of this convention and has ratified the convention. Thus, Indonesia should comply with the provisions in the LOSC. The question is has Indonesia exercised itssovereignty over the EEZ? This paper argues that the implementation of imprisonment in Indonesian EEZ contradicts both Indonesian laws and international law of the sea.Key words: imprisonment, EEZ, sovereignty and sovereign rights